Community centres in increasingly diverse neighbourhoods: Policies and practices of community building in post-war housing estates in Switzerland - Althaus, Eveline (2022)
This paper uses research conducted in Swiss post-war high-rise estates to focus on policies and practices of community building in neighbourhoods with an increasingly diverse population. Initially, the estates were mainly populated by Swiss and Southern European lower to middle income families, but latterly the household structures have become very heterogeneous with residents coming from all over the world. The planning and development policies of the estates are based on specific ideas about creating a community, which are still evident in the building and management of community centres but also in various facilities for common use (playgrounds, football and sport fields, community rooms and kitchens, libraries, petting zoos, cafés, crafts rooms, etc.). The community centres, along with community work, are key to encouraging encounters, connecting people and activating cultural life in the neighbourhoods and have played a pioneering role far beyond the boundaries of their respective estates. However, individualisation and pluralisation processes, the aging of the facilities and built structures, and economic pressures pose challenges for the community centres. The current Covid-19 crisis reinforces these challenges by limiting and impeding cultural activities and direct (physical) social encounters. The paper analyses the potential and the challenges of community building in the context of growing diversity among residents, and acknowledges what we can learn from these experiences when thinking about creating and strengthening communities in a multi-faceted world today.